Marketing activities and customer satisfaction survey of Holcim (Bangladesh) Ltd. - Khan, A.U.M.Golam Raihan (BRAC University, 2010)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2008.